DUKUNGAN SOSIAL TERHADAP DRIVER OJEK ONLINE DI KOTABANDUNG PADA MASA PANDEMI COVID-19 - Farhan Firdausi, - (2020)
This study aims to see the social support received by online motorcycle drivers during the pandemic. The research sample was an online motorcycle driver in Bandung. Methods of data using quantitative descriptive methods. The measuring tool uses the Social Provisions Scale compiled by Weiss (in Cutrona & Russel 1984). Data were analyzed using the computerized SPSS (Statistical Product and Service Solution), release 22.0 for windows. From the data obtained from 429 samples, it was found that more than half of the sample (52%) felt high social support, while as many as 48% felt low social support. From the data analysis, it was found that there was no significant difference in social support between the male and female sex groups. In marriage, there is also a difference in social support that is not significant. Lastly is the groups that follow the community and non-communities, from the results of the calculation, there is no significant difference in social support between these groups.